A signal-on split aptasensor for highly sensitive and specific detection of tumor cells based on FRET. Issue 8 (10th December 2015) - Yuan, Baoyin; Zhou, Yu; Guo, Qiuping; Wang, Kemin; Yang, Xiaohai; Meng, Xiangxian; Wan, Jun; Tan, Yuyu; Huang, Zhixiang; Xie, Qin; Zhao, Xiayu
Abstract : The split aptasensor for highly sensitive and specific detection of tumor cells based on FRET. Abstract : We present here a signal-on fluorescence biosensor for highly sensitive and specific detection of tumor cells with a split aptamer based on fluorescence resonance energy transfer (FRET). This sensor holds considerable potential for simple, rapid, sensitive and specific tumor cell detection in early clinical diagnosis.